Clinical-year Students’ Competency in Chest X-ray Interpretation: A Theoretical-based Intervention - Tarek Hegazi; Khalid Kurdi; Abdulaziz Alfayez; Ali Alhammad; Abdullah Aldakheel; Rakan Alshahrani; Ghazi Alotaibi; Muhannad AlQahtani; Mu’taman Jarrar; Hussain Abu Al Ola; Abdulmohsen Al Elq (Saudi Journal of Medicine and Medical Sciences)
Background: Chest radiography is important in detecting chest abnormalities, an essential skill for medical students during their transition into clinical years. Although critical, limited research has evaluated students’ competencies in chest X-ray interpretation, a recognized area of weakness. Objectives: This study aims to (1) assess medical students’ competencies and confidence in chest X-ray interpretation, (2) measure the effectiveness of an educational intervention, and (3) determine the influence of clinical history on students’ decision-making. Materials and Methods: This experimental pre- and post-design study included clinical-year students from College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia, and was conducted between November 2022 and April 2023. It was executed in three phases: pre-intervention assessment, an intervention involving a lecture based on Thomas and Kern’s six-step approach, and a post-intervention assessment. Results: The study comprised 77 students. Mean self-reported knowledge and confidence scores were 3.08 ± 0.6 and 2.78 ± 0.7, respectively. There was a significant difference in the mean scores for the pre-test without clinical history (6.29 ± 2.38) compared with the pre-test with clinical history scores (8.58 ± 2.65) (P < 0.001). Post-intervention scores were also significant (9.40 ± 2.91) compared to both pre-tests without and with clinical history (P < 0.001 and 0.034, respectively). Students exhibited high accuracy in diagnosing pneumoperitoneum with and without clinical history (88% and 97%, respectively). Confidence scores were elevated when clinical history was provided and the students had access to their patients’ histories. Conclusions: A lecture-based intervention built on Thomas and Kern’s approach markedly enhanced students’ capacities to interpret chest X-rays. Integrating clinical history proved beneficial, underscoring the necessity for comprehensive teaching methodologies in medical education.